Decentralized H∞ Control for Large-Scale Systems with Uncertain Missing Measurements Probabilities. (1st October 2015) - Zhou, Ying; Zang, Qiang; Fan, Chunxia
Abstract : For large-scale systems which are modeled as interconnection ofN networked control systems with uncertain missing measurements probabilities, a decentralized state feedbackH ∞ controller design is considered in this paper. The occurrence of missing measurements is assumed to be a Bernoulli random binary switching sequence with an unknown conditional probability distribution in an interval. A state feedbackH ∞ controller is designed in terms of linear matrix inequalities to make closed-loop system exponentially mean square stable and a prescribedH ∞ performance is guaranteed. Sufficient conditions are derived for the existence of such controller. A numerical example is also provided to demonstrate the validity of the proposed design approach.